Power-efficient LDPC code decoder architecture - Shimizu, K; Togawa, N; Ikenaga, T; Goto, S (ISLPED '07 : proceedings of the International Symposium on Low Power Electronics and Design : Portland, Oregon, USA, August 27-29, 2007, 2007)
This paper proposes the power-efficient LDPC decoder architecture which features (1) a FIFO buffering based rapid convergence schedule which enables the decoder to accelerate the decoding throughput without increasing the required number of memory bits, (2) an intermediate message compression technique based on a clock gated shift register which reduces the read and write power dissipation for the intermediate messages. Simulation results show that the proposed decoder achieves 1.66 times faster decoding throughput, and improves the power efficiency (which is defined by the power dissipation per Mbps) up to 52% compared to the decoder based on the conventional overlapped schedule.